Modified centrifugal technique for determining polymer demand and achievable dry solids content in the dewatering of anaerobically digested sludge. Issue 53 (13th November 2016) - To, Vu Hien Phuong; Nguyen, Tien Vinh; Vigneswaran, Saravanamuthu; Duc Nghiem, Long; Murthy, Sudhir; Bustamante, Heriberto; Higgins, Matthew
Abstract: This study aims to characterize anaerobically digested sludge (ADS) and correlate the sludge characteristics in terms of soluble organic compounds with polymer demand (PD) during sludge conditioning. The PD required to achieve maximum dewatering of the ADS studied is in the range of 8–10 kg polymer/dry ton. The commonly used capillary suction time parameter to evaluate the solid–liquid separation ability was not a reliable indicator for assessing dewatering. Instead, in this study, a modified centrifugal technique proposed by Higgins (Higgins MCT) was used to assess the maximum achievable dry solids content of the biosolids cake. The Higgins MCT is readily obtained using a bench-scale centrifuge equipped with a modified centrifuge bucket. Using the Higgins MCT, the maximum dry solids contents obtained from conditioned ADS was 30 wt%. These values were comparable to the dry solids content obtained from the same sludge at full-scale level. Our results suggest Higgins MCT is suitable for assessing the final dry solids content and simulating the dewatering process.